2012
DOI: 10.1007/s11064-011-0685-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Administration of the Vinyl Chalcogenide 3-Methyl-1-phenyl-2-(phenylseleno)oct-2-en-1-one on Oxidative Stress in Different Brain Areas of Rats

Abstract: Selenium (Se) is an essential mineral for mammals. It is a nutrient related to the complex metabolic and enzymatic functions. Although Se has important physiological functions in the cells, organic compounds of Se can be extremely toxic, and may affect the central nervous system. This study aims to investigate the effect of the chronic treatment with the vinyl chalcogenide 3-methyl-1-phenyl-2-(phenylseleno)oct-2-en-1-one on some parameters of oxidative stress in the brain of rats. Animals received the vinyl ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Reasons for decreased organic Se levels in CSF of our ALS patients are unclear, since they cannot be ascribed to a low Se supply, due to the higher amount of inorganic Se available. Two possibly interrelated hypotheses may be advanced: the role of unknown genetic or non-genetic factors in reducing the antioxidant response, or the ability of pro-oxidant Se species, including selenite, to reduce expression of Se containing enzymes (Tallandini et al, 1996; Branco et al, 2012; Medeiros et al, 2012), possibly through the induction of oxidative stress (Suryo Rahmanto et al, 2012). On the other hand, in other investigations selenite has been shown to increase brain GPx activity as well as lipid perodixation (Glaser et al, 2010), the latter effect being possibly the cause of the former, and in human and in vitro studies it appears to increase SePP levels (Meplan et al, 2009; Hoefig et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for decreased organic Se levels in CSF of our ALS patients are unclear, since they cannot be ascribed to a low Se supply, due to the higher amount of inorganic Se available. Two possibly interrelated hypotheses may be advanced: the role of unknown genetic or non-genetic factors in reducing the antioxidant response, or the ability of pro-oxidant Se species, including selenite, to reduce expression of Se containing enzymes (Tallandini et al, 1996; Branco et al, 2012; Medeiros et al, 2012), possibly through the induction of oxidative stress (Suryo Rahmanto et al, 2012). On the other hand, in other investigations selenite has been shown to increase brain GPx activity as well as lipid perodixation (Glaser et al, 2010), the latter effect being possibly the cause of the former, and in human and in vitro studies it appears to increase SePP levels (Meplan et al, 2009; Hoefig et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of dl -selenomethionine to mercury-exposed rat pups whose mothers were also subjected to the same treatment during pregnancy resulted in significant increase in hippocampal SOD activity (Su et al 2008). Medeiros et al (2012) found that selenoorganic compound of chain structure increased SOD activity only in the rat hippocampus, whereas GPx was reduced in all studied brain structures (cerebral cortex, hippocampus and cerebellum). In the present experiment the same result was obtained with regard to GPx in group III receiving chain selenocompound.…”
Section: Discussionmentioning
confidence: 97%
“…Administration of selenium, in form of two organic compounds (selenones), to rats exposed to carcinogenic hydrocarbon resulted in distinct decrease in MDA concentration (Selamoglu Talas et al 2008). Organoselenium compound of chain structure did not influence in well-marked way TBARS in rat hippocampus and cerebellum, whereas enhancement in the cerebral cortex was observed (Medeiros et al 2012). Insignificant increase was observed in the present work in group IV, but the time of administration was considerably shorter (10 vs. 30 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms underlying Se toxicity is still not completely understood. The toxicology of organoselenium compounds is mediated at least in part by their ability to react with thiol groups from biologically active molecules and the capacity of the Se compounds to induce the formation of reactive species in many tissues such as brain, heart, liver and kidney …”
Section: Introductionmentioning
confidence: 99%